Efficacy and safety of total glucosides of paeony as an add-on treatment in adolescents and adults with chronic urticaria: A systematic review and meta-analysis - Li, Ming; Li, Yan; Xiang, Lujing; Li, Linfeng (Frontiers in Pharmacology, 2022)
Background: Total glycosides of paeony (TGP), an active compound extracted from the dried roots of Paenoia lactiflora Pall., has been widely used to treat chronic urticaria (CU) in China. This study aims to systematically evaluate the efficacy and safety of TGP as an add-on treatment for the treatment of CU in adolescents and adults. Methods: Eight literature databases and two clinical trial registries were searched from their inception to May 31, 2022. Randomized controlled trials on TGP as an add-on treatment for CU in adolescents and adults were included. The Cochrane Collaboration’s risk of bias tool was used for the methodological quality assessment, and RevMan 5.3 software and Stata 12.0 software were used for data analyses. Results: A total of 30 studies with 2973 participants were included in this meta-analysis. The methodological qualities of all included studies were suboptimal. The pooled results showed that TGP combined with H1-antihistamine was superior to H1-antihistamine alone in the cure rate (risk ratio (RR) =1.54, 95% confidence interval (CI) =1.39 to 1.71, P<0.00001), total efficacy rate (RR=1.33, 95%CI=1.26 to 1.40, P<0.00001), urticaria activity score 7 (mean difference (MD) = -4.03, 95%CI= -6.62 to -1.44, P=0.002), recurrence rate (RR=0.31, 95%CI= 0.20 to 0.46, P<0.00001), and the level of IgE in serum (standardized mean difference (SMD) =-1.96, 95%CI= -3.02 to -0.90, P=0.0003). In terms of safety, the incidence of diarrhea (RR=6.19, 95%CI=3.39 to 11.29, P<0.00001) was significantly increased in the TGP plus H1-antihistamine groups, and no abnormal results of laboratory tests and electrocardiogram were reported in two groups. The qualities of evidences were evaluated as moderate to low. Conclusions: TGP as an add-on treatment could provide a good effect for CU in adolescents and adults with mild and tolerable adverse events. However, in view of poor methodological quality, high-quality and long-term clinical trials are needed in the future to confirm and update the evidence.